2018
DOI: 10.1186/s12886-018-0688-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of switching to aflibercept using a pro re nata treatment regimen in patients with neovascular age-related macular degeneration who incompletely responded to ranibizumab

Abstract: BackgroundTo assess the effect of switching patients previously incompletely treated with ranibizumab (RBZ) to aflibercept (AFL) using a pro re nata (PRN) treatment strategy in neovascular age-related macular degeneration (nvAMD).MethodsA retrospective case series was conducted on patients who had persistent or recurrent intra- and/or sub-retinal fluid treated initially with RBZ and subsequently switched to AFL. The main outcome measures were best corrected visual acuity (BCVA) and central retinal thickness (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…In accordance to the literature (26)(27)(28)(29)(30)(31), our results show a benefit of a therapy switch to aflibercept for patients' refractory to ranibizumab. Only one study showed visual acuity improvement after aflibercept injection according to a fixed regimen (28). All other papers demonstrated a stable or worse visual acuity despite reduced retinal prominence or PED height, with various injection regimens applied (PRN, fixed, treat and extent).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance to the literature (26)(27)(28)(29)(30)(31), our results show a benefit of a therapy switch to aflibercept for patients' refractory to ranibizumab. Only one study showed visual acuity improvement after aflibercept injection according to a fixed regimen (28). All other papers demonstrated a stable or worse visual acuity despite reduced retinal prominence or PED height, with various injection regimens applied (PRN, fixed, treat and extent).…”
Section: Discussionsupporting
confidence: 92%